Resistive Switching Memory: Lead‐Free Dual‐Phase Halide Perovskites for Preconditioned Conducting‐Bridge Memory (Small 41/2020). Issue 41 (15th October 2020) - Han, Ji Su; Le, Quyet Van; Kim, Hyojung; Lee, Yoon Jung; Lee, Da Eun; Im, In Hyuk; Lee, Min Kyung; Kim, Seung Ju; Kim, Jaehyun; Kwak, Kyung Ju; Choi, Min‐Ju; Lee, Sol A; et al.
Abstract : In article number 2003225, Soo Young Kim, Ho Won Jang, and co‐workers successfully fabricate preconditioned resistive switching memory devices using lead‐free dual‐phase halide perovskites. The devices show filamentary resistive switching behavior involving Ag cations in halide perovskites with ultra‐low operating voltages, and high on/off ratio.